Supernatural. Season six [videorecording (DVD)] - Padalecki, Jared, 1982-; Ackles, Jensen; Kripke, Eric (Warner Home Video, 2011)
The prize: ending the Apocalypse. The price: Sam's life. Season 5's horrific finale left Dean alone as Sam descended into Hell. Now a different man, Dean vows to stop hunting and devote himself to building a family with Lisa and her son Ben. Then, mysteriously, Sam reappears, drawing Dean back into the old life. But Sam's a different man too. He's returned without his soul.